Persepsi Petani Terhadap Program Kemitraan Tanam Bawang Putih dengan PT. Fajar Mulia Transindo di Kecamatan Tawangmangu Kabupaten Karanganyar - Imaduddin Xena; Suminah Suminah; Agung Wibowo (Jurnal Indonesia Sosial Sains, 2021)
This research described garlic planting partnership program, described farmers’ perception on garlic planting partnership program, and analysed factors which influenced farmers’ perception on garlic planting partnership program. Basic method of the research used was quantitative with survey technique. The research location was in Nglebak Village and Sepanjang Village, Tawangmangu Sub-district, Karanganyar Regency, with Gapoktan consideration in Nglebak Village and Sepanjang Village that was one of Gapoktan followed garlic planting partnership program with Fajar Mulia Trasindo Ltd. The sampling used technique of purposive random sampling that consisted of 60 respondents. The data analysis used multiple linear regression test with SPSS Statistics 25.0 program. The research result showed that: (1) garlic planting partnership program that was done by Gapoktan in Sepanjang Village and Nglebak Village, Tawangmangu Sub-district with private party namely Fajar Mulia Trasindo Ltd. has occured since 2017. This program was based on partnership principle in order to be mutually beneficial between two parties. (2) farmers’ perception on garlic planting partnership program with Fajar Mulia Trasindo Ltd. in Tawangmangu Sub-district included in bad category, it was due to unsatisfactory result that was obtained by farmers in garlic planting partnership program which have been implemented, among others, the lateness of seed supply, the low quality of seeds given so that it influenced their garlic harvest. (3) partially or together in independent variable (self-concept, needs, experience, hope, novelty, intensity, and proximity) it did not be significantly influenced towards dependent variable (farmers’ perception on garlic planting partnership program).